Point of danger [large type] - Hannon, Irene (Hannon, Irene. Triple threat, 2021)
Radio talk show host Eve Reilly is used to backlash from her pot-stirring on-air commentary and interviews, but now it seems a disgruntled listener is resorting to more than angry words to express their displeasure. When a suspicious package arrives on her doorstep, Eve turns to law enforcement for help. Police detective Brent Lange can't find any evidence to link the string of unsettling incidents that follows, but he's convinced they're connected.